Using flow disruptions to understand healthcare system safety: A systematic review of observational studies. (January 2022) - Cohen, Tara N.; Wiegmann, Douglas A.; Kanji, Falisha F.; Alfred, Myrtede; Anger, Jennifer T.; Catchpole, Ken R.
Abstract: This systematic review provides information on the methodologies, measurements and classification systems used in observational studies of flow disruptions in clinical environments. The PRISMA methodology was applied and authors searched two databases (PubMed and Web of Science) for studies meeting the following inclusion criteria: (a) were conducted in a healthcare setting, (b) explored systems-factors leading to deviations in care processes, (c) were prospective and observational, (d) classified observations, and (e) were original research studies published in peer-reviewed journals. Thirty studies were analyzed and a variety of methods were identified for observer training, data collection and observation classification. Although primarily applied in surgery, comparable research has been successfully conducted in other venues such as trauma care, and delivery rooms. The findings of this review were synthesized into a framework of considerations for conducting rigorous methodological studies aimed at understanding clinical systems. Highlights: There is variability in methodologies of observational flow disruption studies in healthcare. We aimed to compare methodologies, measurements and classification systems used. We aimed to consolidate an understanding of this research and potential next steps. This review may help generate best practices for research on clinical system function.